Feasibility of capillary velocity assessment by statistical means using dual-beam spectral-domain Optical Coherence Tomography: a preliminary study - Daly, Susan M.; Silien, Christophe; Leahy, Martin J. (Journal of biophotonics, 2013)
The assessment of vascular dynamics has been shown to yield both qualitative and quantitative metrics and thus play a pivotal role in the diagnosis and prognosis of various diseases, which may manifest as microcirculatory irregularities. Optical Coherence Tomography (OCT) is an established imaging modality which utilises the principle of optical interferometry to distinguish between spatial changes in refractive index and thus formulate a multi‐dimensional representation of a specimen in vivo. Nonetheless, difficulties remain in obtaining accurate data (morphological and/or transient) in an environment which is subject to such large biological variability. In an effort to address the issue of angular dependence as with Doppler based analysis, a dual‐beam Spectral‐domain OCT system for quasi‐simultaneous specimen scanning is described. A statistical based method of phase correlation is outlined which is capable of quantifying velocity values in addition to the ability to discern bidirectionality, without the necessity of angular computation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)